What influences natural gas consumption in China: A closer look at their marginal and lag effects. (20th August 2022) - Qin, Manman; Sun, Renjin; Hu, Dongou; Dong, Kangyin; Zhong, Huaxin
Abstract: Natural gas is a crucial transitional energy for China to achieve the emission reduction goal for the sustainable development of the economy. In order to more accurately analyze the relationship between natural gas consumption and economic development, this paper fully considers the lag effect of natural gas consumption driving factors, including resource scarcity, environmental regulation, and technological development. Firstly, stepwise regression method is used to select driving factors to ensure the validity of the marginal effect model, considering of the possibility of multiple collinearities in marginal model. Secondly, quantile regression model and impulse response functions in vector autoregressive model are applied to estimate the marginal and lag effects of factors on natural gas consumption. The results show that gross domestic product is the most critical driving factor of natural gas consumption, and its coefficient is the highest, far higher than technological development. It has the largest lag effect on natural gas consumption, and has a great influence on itself in the first stage of lag. Resource scarcity and environmental regulation have negative effects on natural gas consumption, but only exist in the first lag stage. Highlights: Fully considering the lag effect of natural gas consumption driving factors, including resource scarcity, environmental regulation, and technological development. Quantile regression model and vector autoregressive model are applied to estimate the marginal and lag effects of factors on natural gas consumption. Lag effects of natural gas consumption on itself are the greatest at the first lag phase, followed by gross domestic product. Resource scarcity and environmental regulation have negative effects on natural gas consumption, but only exist in the first lag stage.